(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A pot culture experiment was conducted to study the effects of diazinon pesticide on the availability of heavy metals of plant with the application of different doses of rice hull. For this purpose, an upland leafy vegetable, namely Indian spinach (Basella alba) was used. Seven different treatments including a control following a randomized complete block design (RCBD) were used in the experimental set-up. Three soil and plant sample were taken at three different periods, viz. 6 hours, 15 days and 30 days, after application of the diazinon. The soil and plant samples were analyzed in the laboratory to determine their contents of Fe and diazinon pesticide. The soil contained lower concentration of Fe compared to that of the plant. In most of the cases, soil Fe decreased gradually in the sampling periods. Soil diazinon content increased and then decreased at third sampling period for all treatments. The rice hull as bioremediant was able to restrict the uptake of diazinon by plants and could bring the pesticide into the soil system. The application of diazinon initially affected soil, but it disappeared gradually from the soil with time due to degradation, evaporation and transportation. At second sampling period, the diazinon content was highest in both soil and plant. The present study showed positive response of rice hull as bioremediation and this finding can be used to minimize the harmful effects of pesticide. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 57-62